Interactions of Hydrogen Atoms with Acceptor–Dioxygen Complexes in Czochralski‐Grown Silicon. Issue 17 (29th May 2022) - Abdul Fattah, Tarek O.; Markevich, Vladimir P.; De Guzman, Joyce Ann T.; Coutinho, José; Lastovskii, Stanislau B.; Hawkins, Ian D.; Crowe, Iain F.; Halsall, Matthew P.; Peaker, Anthony R.
Abstract : It is debated in the silicon PV community whether or not the presence of hydrogen is essential for the permanent suppression ("regeneration") of the recombination activity of the boron–oxygen (BO) defect, which is responsible for light‐induced degradation (LID) of solar cells produced from B‐doped oxygen‐rich silicon. The BO‐LID defect has been identified as a Bs O2 complex which has negative‐ U properties. This study focuses on the interactions of hydrogen with the Bs O2 defect to elucidate the BO‐LID regeneration mechanism. With the use of junction spectroscopy techniques, the changes in concentration of the Bs O2 donor state in diodes which are fabricated on Czochralski‐grown (Cz) B‐doped Si and subjected to hydrogenation and subsequent heat treatments have been monitored. It is found that annealing of the hydrogenated Cz‐Si:B diodes in the temperature range 398–448 K under the application of reverse bias (RBA) results in nearly total disappearance of the Bs O2 defect. It is argued that electrically neutral Bs O2 –H complexes have been formed upon the RBA treatments. According to ab initio calculations, the binding energy of H + to Bs O2 − exceeds that of H + to Bs − by at least 0.1 eV, and the resulting Bs O2 –H complexes are electrically inactive. Abstract : Whereas the regeneration of the Bs O2 defect cannot occur in the absence of hydrogen, clear evidence of the interactions of hydrogen atoms with the Bs O2 complexes in hydrogenated Cz‐Si:B material has been obtained. This results in the formation of electrically neutral Bs O2 –H complexes and, thus, elimination of light‐induced degradation (LID) of solar cells from Si:B + O material.